Do Financing Constraints Matter for Outward Foreign Direct Investment Decisions? Evidence from India - Subash Sasidharan; M. Padmaja (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2016)
This study examines the role of financing constraints in explaining outward FDI decisions using unique firm level panel data on Indian manufacturing during the period 2007-2014. We consider the role of both internal finance and external finance in firm decisions on outward FDI and employ instrumental variable probit model to examine financing constraints in outward FDI decisions of firms. Further, using count data models, we examine financing constraints in determining strategies regarding number of affiliates abroad. The study shows that firms with higher cash flow and liquidity are likely to have more number of foreign affiliates.
hdl:10398/9296
Keywords: 330; Financing constraints; Outward FDI; Total factor productivity; Unternehmensfinanzierung; Liquiditätsbeschränkung; Auslandsinvestition; Indisch; IV-Schätzung; Indien